2015
DOI: 10.1038/nchembio.1990
|View full text |Cite
|
Sign up to set email alerts
|

Photo-lysine captures proteins that bind lysine post-translational modifications

Abstract: Post-translational modifications (PTMs) have key roles in regulating protein-protein interactions in living cells. However, it remains a challenge to identify these PTM-mediated interactions. Here we develop a new lysine-based photo-reactive amino acid, termed photo-lysine. We demonstrate that photo-lysine, which is readily incorporated into proteins by native mammalian translation machinery, can be used to capture and identify proteins that recognize lysine PTMs, including 'readers' and 'erasers' of histone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 25 publications
1
75
0
Order By: Relevance
“…Carbene-based cross-linking strategy, which rapidly immobilizes molecules in random orientation due to its high and diverse chemical reactivity (e.g., carbon insertion, Michael addition, nucleophilic reaction, etc. ), is becoming an optimized immobilization method for microarray fabrications (14)(15)(16). Meanwhile, due to its high loading capacity for biomolecules and antifouling properties, 3D polymer surface with a designed structure often shows high signal-to-noise ratio in SPRi (17)(18)(19).…”
Section: Significancementioning
confidence: 99%
“…Carbene-based cross-linking strategy, which rapidly immobilizes molecules in random orientation due to its high and diverse chemical reactivity (e.g., carbon insertion, Michael addition, nucleophilic reaction, etc. ), is becoming an optimized immobilization method for microarray fabrications (14)(15)(16). Meanwhile, due to its high loading capacity for biomolecules and antifouling properties, 3D polymer surface with a designed structure often shows high signal-to-noise ratio in SPRi (17)(18)(19).…”
Section: Significancementioning
confidence: 99%
“…It therefore appeared desirable to introduce the diazirine tag into positions that would allow probing the vicinity of polar groups that are engaged in non‐covalent bonding in peptide complexes. Recently, a lysine residue called photolysine, containing the diazirine ring in the side chain, has been reported that addressed this need . However, photolysine is obtained by a multistep synthesis and is not readily available for studies of peptide complexes.…”
Section: Methodsmentioning
confidence: 99%
“…Fortunately, other photoreactive UAAs are available. These include a diazirine-containing analogue of lysine, termed photolysine, 49 which generates a reactive carbene species upon UV irradiation. This photoreactive amino acid can be nonspecifically incorporated into cellular proteins by simply including the UAA in the cell culture medium—the high lysine content of histones makes them well suited to this approach.…”
Section: Chemical Approaches For Modifying Chromatin In Cellsmentioning
confidence: 99%